Lynds Bright Nebulae: sites of possible twisted filaments and ongoing star formation. Issue 4 (24th July 2021) - Dewangan, L K; Dhanya, J S; Bhadari, N K; Ojha, D K; Baug, T
ABSTRACT: The paper presents an analysis of multiwavelength data of two Lynds Bright Nebulae (LBNs), LBN 140.07+01.64 and LBN 140.77−1.42. The 1420-MHz continuum map reveals an extended Y-shaped feature (linear extent ∼3.7°), which consists of a linear part and a V-like structure. The sites LBN 140.07+01.64 and AFGL 437 are located towards the opposite sides of the V-like structure, and LBN 140.77−1.42 is spatially seen towards the linear part. Infrared-excess sources are traced towards the entire Y-feature, suggesting star formation activities. Infrared and submillimetre images show the presence of at least two large-scale dust filaments extended towards the LBN sources. The Herschel maps, which are available only towards the northern and central parts of the Y-feature, display the presence of higher column density (≥2.4 × 10 21 cm −2 ) of materials towards the filaments. Using the 12 CO(1–0) line data, the distribution of molecular gas at [−42.7, −34.4] km s −1 traces the cloud associated with the Y-feature, and confirms the existence of filaments. The large-scale filaments appear to be possibly spatially twisted. There is a hint of an oscillatory-like velocity pattern along both the filaments, favouring their proposed twisted nature. It is the first study showing the possible twisting of filaments, which is more prominent in the northern and central parts of the Y-feature. This possible twisting/coupling of the large-scale filaments appears to be responsible for the observed star formation (including known OB stars). The proposed physical process and the energetics of OB stars together seem to explain the origin of the ionized Y-feature.